Comparison of the reducing effects of blueberry and propolis extracts on heterocyclic aromatic amines formation in pan fried beef. (April 2022) - Gumus, Damla; Kizil, Mevlude
Abstract: This study was aimed to examine the effects of natural antioxidant-based marinades on the formation of heterocyclic aromatic amines (HAAs) in cooked beef. Samples were marinated overnight with different concentrations (0, 0.25, 0.5 and 1%) of blueberry or propolis extracts, and pan fried at 150 and 200 °C for a total of 10 min. Individual and total HAAs were detected at different levels according to the cooking temperature, extract type and concentration. Total HAA levels increased as the cooking temperature increased ( P  < 0.01), and ranged from non detectable levels to 38.27 ng/g across all samples analysed. Mitigation up to 61.2% and 100% in total HAA levels were achieved by propolis and blueberry extracts, respectively. The inhibitory effects of blueberry extract on total HAAs formation were significantly higher than propolis extract ( P  < 0.01). Thereby, this study showed that natural antioxidant-based marinades containing blueberry and propolis extracts had mitigating effects on HAAs formation in beef samples pan-fried at 150 and 200 °C. Highlights: Effects of marinades containing different concentrations of blueberry and propolis extracts on HAA formation were examined. Blueberry and propolis extracts reduced total HAA levels in pan fried beef. The inhibitory effects of blueberry extract on total HAA formation were significantly higher than propolis extract. Marinating beef with blueberry and propolis prior to cooking might be an effective strategy for inhibition of HAA formation.